2000. Rapid, Point-of-care Diagnosis of Tuberculosis with Novel Truenat Assay: Cost-Effectiveness and Budgetary Impact Analysis for India's Public Sector. (26th November 2018) - Lee, David J; Kumarasamy, Nagalingeswaran; Resch, Stephen; Sivaramakrishnan, Gomathi N; Mayer, Kenneth; Tripathy, Srikanth; Paltiel, A David; Freedberg, Kenneth; Reddy, Krishna P
Abstract: Background: Point-of-care (POC) tuberculosis (TB) diagnostics may dramatically improve TB outcomes. Truenat is a new, battery-powered RT-PCR device that rapidly detects TB and rifampin resistance. Due to its portability, it may be valuable in peripheral healthcare settings. We evaluated the cost-effectiveness of Truenat in peripheral laboratories (designated microscopy centres [DMCs]) and public healthcare facilities in India. Methods: We used the CEPAC-International microsimulation model to compare four TB diagnostic strategies for adult, HIV-negative patients with suspected TB: (1) sputum smear microscopy in DMCs (SSM); (2) Xpert MTB/RIF in DMCs (Xpert); (3) Truenat in DMCs (Truenat DMC); and (4) Truenat in public healthcare facilities (Truenat POC). We projected life expectancy (LE), costs, incremental cost-effectiveness ratios (ICERs), and 5y budget impact of full scale-up. A strategy was cost-effective if its ICER was <US990/year of life saved (YLS) (i.e., <50% of India annual per capita GDP). Model inputs included: TB prevalence, 20%; sensitivity for TB detection, 92% for Xpert and 89% for Truenat; costs per test, 12.70 for Xpert and 13.20 for Truenat; linkage to care after diagnosis, 84% for DMC-based tests and 95% for POC. We varied these parameters in sensitivity analyses. Results: Compared with SSM, other strategies increased TB case detection by >6%; Truenat POC increased LE by 0.3 years with ICER 210/YLS (Table 1). Compared with Xpert, Truenat DMC decreased LE and cost, but Truenat POC improved LE by 0.05 years and was cost-effective. In multi-way sensitivity analysis at 5 years horizon, Truenat POC, at 89% diagnostic sensitivity and linkage to care >86%, was cost-effective and sometimes cost-saving compared with Xpert (Figure 1). The cost-effectiveness of Truenat, relative to Xpert, depended on the interplay of sensitivity and linkage to care. Public-sector implementation of Truenat POC increased healthcare expenditures by 360 million compared with full scale-up of Xpert (Figure 2). Treatment costs, not diagnostic test costs, accounted for most of the difference. Conclusion: When used at the point of care, Truenat for TB diagnosis should improve linkage to care, increase LE, and be cost-effective compared with SSM or Xpert and, thus, should be more widely utilized in India. Disclosures: All authors: No reported disclosures.